α-synuclein interacts with SOD1 and promotes its oligomerization - Helferich, Anika Marie; Ruf, Wolfgang P.; Grozdanov, Veselin; Freischmidt, Axel; Feiler, Marisa S.; Zondler, Lisa; Ludolph, Albert C.; McLean, Pamela J.; Weishaupt, Jochen H.; Danzer, Karin M. (Molecular neurodegeneration, 2015)
Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS) are both neurodegenerative diseases leading to impaired execution of movement. α-Synuclein plays a central role in the pathogenesis of PD whereas Cu, Zn superoxide dismutase (SOD1) is a key player in a subset of familial ALS cases. Under pathological conditions both α-synuclein and SOD1 form oligomers and fibrils. In this study we investigated the possible molecular interaction of α-synuclein and SOD1 and its functional and pathological relevance.